INDUSTRI KREATIF SELUBUNG BANGUNAN BREEZE BLOCK UNTUK MENDAPATKAN KENYAMANAN TERMAL, NILAI ESTETIKA EKSTERIOR, DAN INTERIOR BANGUNAN - Pranajaya, I Kadek; Mahadipta, Ngurah Gede Dwi; Putra, I Dewa Gede; Dewi, Ni Made Emmi Nutrisia; Dwipa, I Made Karuna (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2021)
The tropical climate has presented challenges for architects and inetior designers to be able to design buildings that can provide optimal comfort for the occupants. Direct sunlight to the building is the main factor that makes the building feel stiflingly hot. One of the architects' strategies to overcome this problem is through the design of a building enevelopes (breeze block) to create cross-ventilation to allow airflow through a room to excess humidity outside and replace it with fresher air. Indoor comfort can be achieved by natural air conditioning using a breeze block. In addition from realizing thermal comfort, breeze blocks can also make building and interior facades more aesthetically pleasing with the form of a creative breeze block design in accordance with its form and function.This study uses descriptive-qualitative methods with data reduction analysis methods. The data presentation technique is carried out in a narrative way with images, photographs and maps.